The Effect of Music Therapy to Lower Pain Scale among Post-Operating Patients - Ade Fitriani; Fidya Anisa Firdaus; Fidiyanti Amatilah; Haryani (Genius Journal, 2021)
Introduction: Postoperative pain is a problem of passen complaints that often occur mostly in hospitals as a consequence of post-surgery that cannot be avoided. The negative effects of pain can be controlled by managing nyen which is a very important part of patient care including the provision of pharmacological therapy and non-pharmacological therapy in the form of cognitive behavioral interventions such as relaxation techniques, music therapy, imagery and biofeedback. Overcoming pain in postoperative patients by providing music therapy. Method: This research method used an experimental design with a literature review approach. The search for articles used 6 journal databases including PubMed, JSTOR Wiley Online Library, Sage Journal and Taylor & Francis Online and Google Scholar as many as 6 articles that met the inclusion criteria were reviewed. All articles were selected using an assessment of articles that met the inclusion criteria, including publication range 2015-2020, in English and Indonesian, open access full text pdf. There are also exclusion criteria, namely book chapters, abstract proceedings and posters. This assessment uses the Critical Appraisal Skills Programmed (CASP) instrument. Result: The selection results obtained 6 articles with 137 respondents with an average age of 24 years. The results of the review show that the music therapy method has a positive effect on helping to overcome pain in the nursing process for postoperative patients. Conclusion: Conclusion based on the literature review, it can be found that the provision of music therapy has a better activity in postoperative pain management. The suggestion of this literature review is that this music therapy can be applied directly in the hospital which aims to reduce the nyen response to post-patient patients.